SANKSI HUKUM TERHADAP PELAKU KEJAHATAN DENGAN HYPNOSIS - Prasetyo, Bhakti (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2011)
Hypnosis crime is a conventional crime that has existed since ancient times until today, although it has been around since before this country turns to date we have not had a clause governing criminal offenses. In Empirical hypnosis crime has a lot going on in Indonesia and has many court decisions are fixed (Incracht) that hypnosis criminal act is a criminal offense. The principle of legality to say that